Strategies for the Integrated and Sustainable Management of Water Resources in the Municipality of Pauna (Boyacá) - Villalobos Gualteros, Juan; Ruiz Martínez, Lida (Ingeniería Solidaria, 2019)
Introduction: This article is the outcome of a research called “Strategies for integrated and sustainable management of water resources”, carried out during 2017 and 2018 in the municipality of Pauna, located in the west of the Department of Boyacá. Problem: The unsustainable use of water resources by the population of the municipality makes it a problem of social and environmental priority. The water in the municipality has been used for more and more numerous purposes that seek to meet the needs that arise from economic and tourist development. Objective: To formulate management strategies for the efficient use of water in the residential, commercial and tourist consumption sectors of the municipality. Methodology: The efficient use of water implies understanding and characterizing the habits, in addition to the consumption sectors, and verifying the water quality, to create environmental management strategies through open type descriptive surveys, and sampling struts were used to assess the variation in water quality. Results: The unsustainable use of water resources is linked to the use of obsolete faucets, increasing demand for development and tourism, and general maintenance of spas. Conclusion: This project seeks to generate a change in the behavior of the use towards efficiency, and the modification of the practices of the users to favor the sustainability of the inhabitants. Originality: Strategies of integrated and sustainable management of water resources are formulated for the first time in the municipality of Pauna. Limitations: The lack of information provided by the municipality, and access to the sampling points.